3
\$\begingroup\$

I'm following the MIT lectures on circuits and electronics. They introduce the Thevanin method for solving linear systems in lecture 3 (https://youtu.be/RsJ1eg7XNVs?t=46m49s).

I can't seem to get same results using the Thevenin method as with the node method in this circuit when calculating the voltage e in this circuit:

circuit http://oi57.tinypic.com/2gtx7co.jpg

This is my result with the node method:

$$ 0 = (e - V) * \dfrac{1}{R_1} + e * \dfrac{1}{R_2} - I $$ $$ e = V * \dfrac{R_2}{R_1 + R_2} + I * \dfrac{1}{\dfrac{1}{R_1}+\dfrac{1}{R_2}} $$ $$ e = V * \dfrac{R_2}{R_1 + R_2} + I * \dfrac{R_1*R_2}{R_1+R_2} $$

But when I try to use the Thevenin method, I get a different answer.

First, I convert the part of the circuit with R2 and I:

circuit http://oi61.tinypic.com/2ibkk81.jpg

Where:

$$ T_{th} = I * R_2 $$ $$ R_{th} = R_2 $$

Then, after combining the voltage sources, I use voltage divider to find the voltage across Rth:

$$ e = (V - I * R_2) * \dfrac{R_2}{R_1 + R_2} $$ $$ e = V * \dfrac{R_2}{R_1 + R_2} - I * \dfrac{(R_2)^2}{R_1 + R_2} $$

I must have done something wrong here. Why do I get different values for e?

\$\endgroup\$
  • \$\begingroup\$ I'm not sure what's up with the answer you got with Thevenin equivalents yet, but your answer using nodal analysis is correct. \$\endgroup\$ – helloworld922 Sep 20 '15 at 1:04
1
\$\begingroup\$

I have no idea how you got to the second to last equation of yours. However, let's assume you have the circuit with a Thevenin equivalent circuit substituted in only for R2 and I (your \$R_{th}\$ and \$V_{th}\$ are correct).

Several ways to solve this new circuit:

Nodal Analysis

schematic

simulate this circuit – Schematic created using CircuitLab

Assuming current flows "clockwise" (in the direction of the drawn arrow), performing nodal analysis at node e gives:

\begin{gather} I_{R1} = I_{R2}\\ \frac{V - e}{R_1} = \frac{e - V_{th}}{R_2}\\ R_2 V + R_1 V_{th} = R_1 e + R_2 e\\ e = \frac{R_2 V + R_1 V_{th}}{R_1 + R_2} = \frac{R_2 V + R_1 R_2 I}{R_1 + R_2} \end{gather}

Which is the same answer as you got without using the Thevenin equivalent.

Superposition

See Weezveez's answer. It's the same result.

Mesh Analysis

\begin{gather} V - V_{R1} - V_{R2} - V_{th} = 0\\ V - I_1 R_1 - I_1 R_2 - V_{th} = 0\\ I_1 = \frac{V - V_{th}}{R_1 + R_2}\\ e = V_{th} + V_{R2} = V_{th} + I_1 R_2\\ e = I R_2 + \frac{V - V_{th}}{R_1 + R_2} R_2\\ e = I R_2 + \frac{V - I R_2}{R_1 + R_2} R_2\\ e = \frac{R_2 V + R_1 R_2 I}{R_1 + R_2} \end{gather}

As you can see, all of these methods give the same answer.

\$\endgroup\$
  • \$\begingroup\$ Ah! Looks like I accidentally moved the ground node when combining the voltage sources. Your diagram makes it perfectly clear. Thank you! \$\endgroup\$ – Robz Sep 20 '15 at 4:11
0
\$\begingroup\$

What I did for the Vth is I used superposition. First I disconnected the voltage source, which creates a short in its place, making the voltage V1=VR1.

schematic

simulate this circuit – Schematic created using CircuitLab

Then, I disconnected the current source, which creates an open link in its place. Since no current can flow from the voltage source to complete a full circuit, the voltage on V2 is simply V2=V.

schematic

simulate this circuit

By superposition, Vth=V1+V2= V+ VR1 So e=(V+VR1)*R2

schematic

simulate this circuit

By voltage division: \$\frac{R2*(Vth)}{R1+R2}=\frac{R2*(V+I*R1)}{R1+R2}=\frac{R2*V}{R1+R2}+\frac{I*R2*R1}{R1+R2}\$

\$\endgroup\$
  • \$\begingroup\$ Cool, so superposition also yields the same as the node approach. I still want to know where I went wrong with the Thevenin method. \$\endgroup\$ – Robz Sep 20 '15 at 4:05

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.